Chronochat Visualizer: A Forensic Visualization Tool for WhatsApp Chat Data with Timeline Analysis - Hassan, Noor Hazwalyena; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2025)
WhatsApp is a well-known instant messaging service that is widely used around the world. However, analysing and visualising WhatsApp chat data can be challenging task due to increasing crimes cases involving WhatsApp, unstructured raw data, and limited features from existing tools. In this study, Chronochat Visualizer, a forensic timeline visualization tool is proposed. Chronochat Visualizer allows users to import WhatsApp chat data and visualise the timeline of the chat, including the frequency of the messages, the contact information, and the number of messages sent and received. The Object-Oriented Programming model was adopted to develop the Chronochat Visualizer system, which includes modules such as read file module, analysis module, and report module. The testing result of Chronochat Visualizer offers a smooth and user-friendly experience for users to upload, visualise, and export the WhatsApp chat data. In conclusions, Chronochat Visualizer able to find and pull-out useful data, trends, anomalies to solve the case.